Programa “Ciência sem Fronteiras”: geopolítica do conhecimento e o projeto de desenvolvimento brasileiro - Rogéria Campos de Almeida Dutra; Leonardo Francisco de Azevedo (Ciências Sociais Unisinos)
This paper aims to investigate the growing internationalization of higher education by examining the federal government’s Science without Borders Program, highlighting the academic debate on topics such as territorial boundaries and flows, globalization and geopolitics of scientific knowledge. It also aims at analyzing this program on the basis of official speeches and news present in the mainstream media, observing its conception, forms of participation and early developments. As a method, we used literature review and documental research in order to see how the Science without Borders Program, although strategic for Brazil’s development as an important nation of the Southern Hemisphere, reproduces conventional values. Far from questioning the current Western model of development, it is based on the center-periphery model and on the supremacy of natural science as a way of integrating our country into the valued industrial and technological routes of the world system.